(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
Educators all across the world are starting to worry more and more about the effects of blended learning when mixed with other methods. With its accessibility from anywhere, its ability to accommodate multiple users, and its overall ease of use, blended learning has emerged as a promising new educational medium. This research aimed to discover how effective a Cooperative Learning in a Blended Learning (CLBL) setting is for instructing. Students’ learning outcomes were examined by contrasting CLBL with teacher-led instruction in a BL setting, and students’ reactions to this type of learning environment were studied for patterns. A experimental study was used at the Andalus School of Directorate of Misan Education, Ministry of Eduaction of Iraq in the 2019-2020 academic year. 64 students from the fifth stage were randomly picked over the course of two semesters, with 32 of them being placed in the experimental group and 32 being placed in the control group. A pre-test and a post-test were the primary instruments used to gather the desired data. According to the results of the independent samples t-test, the CLBL environment had a substantial impact on the improvement of students’ volleyball performance. Students who learned in a CLBL environment significantly outperformed those who studied with teacher-led instruction. This was demonstrated by the t-test probability value on the posttest (0.025), which was below than the significance threshold (0.050). In addition, the students were pleased with the efficiency of the CLBL environment and found that it was essential in enhancing their volleyball play.